Unleashing Potentials of Broadcast Technology to Inculcate Ethical Literacy - Waseem, Jawad; Ishaq Ahmed, Muhammad (IJLTP, 2025)
The fast development of broadcast technology is transforming the forms of delivering and transmitting information to mass audiences. The purpose of these technologies is extremely important concerning and promoting moral and ethical values. This study has examined their wide scope of influence and reach as a methodical tool of imparting ethical literacy. Considering the inability of formal education to bring about ethical development, the current study examined the ability of mass media to create ethical developmental processes through a non-formal educational vehicle that imparts moral values, civic responsibility, and social awareness. The research design utilized was a quantitative survey design, which utilized fifty graduate-level students of Allama Iqbal Open University. The data were gathered by means of structured questionnaires and processed by means of descriptive statistics and t-tests. The results have shown that government television channels have a relatively significant effect on moral consciousness as compared to private television and radio channels, the difference of which did not reach statistical significance. A gender analysis also indicated that male respondents tend to indicate more exposure to ethical material on all broadcast media. Such findings highlight the educational capabilities of broadcast media as a secondary process to formal education, which can be used to promote critical reflection, moral reasoning and value re-evaluation across different audiences. This study suggests the strategic inclusion of ethics-oriented interventions as a component of the policy of national broadcasting in order to strengthen the moral growth and the process of life-long learning in the whole socio-cultural continuum of Pakistan.